P188 Sentinel lymph node mapping in vulvar cancer – a new approach with indocyanine green and near infrared fluorescence imaging. (1st November 2019) - Siegenthaler, F; Imboden, S; Papadia, A; Mueller, MD
Abstract : Introduction/Background: The conventional procedure of sentinel lymph node (SLN) mapping in vulvar cancer includes peritumoral injection of technetium-99m radiocolloid (Tc-99m) the day before surgery and intraoperative injection of methylene blue. However, these techniques have some weaknesses. Near infrared (NIR) fluorescence imaging with indocyanine green (ICG) has recently gained popularity in SLN mapping in different types of cancer. The aim of this study is to evaluate the clinical value of ICG SLN mapping in patients with vulvar cancer. Methodology: We retrospectively analyzed all patients at our institution with vulvar cancer undergoing SLN mapping using NIR fluorenscence imaging with ICG by applying video telescope operating microscope (VITOM) system technology between April 2013 and May 2019. Results: 55 groins of 28 patients were analyzed. In 44 groins we used Tc-99m, in four methylene blue and in five both techniques additionally to ICG for SLN detection. ICG was injected peritumorally directly before surgery and no complications due to its administration occurred. 104 SLNs were identified and removed. SLN detection rates were 87.3%, 87.8%, 77.8% and 96.4% for ICG, Tc-99m, methylene blue and the combination of ICG plus Tc-99m, respectively. SLN detection rates of ICG were significantly higher in patients with positive lymph nodes and lymphatic space invasion compared to Tc-99m (p-value 0.035 and 0.005, respectively). We further observed a higher detection rate of ICG in obese patients (94.4% vs. 87.5%); however this observation is non significant (p-value 0.69). Conclusion: Accurate SLN mapping is a crucial part of vulvar cancer staging and enables avoiding unnecessary inguinofemoral lymphadenectomies. SLN mapping with ICG in vulvar cancer is feasible and safe with a detection rate comparable to Tc-99m, particularly in patients with positive lymph nodes, lymphatic space invasion or obesity. Furthermore, it is easier to perform than mapping with Tc-99m and has less side effects compared to methylene blue. Disclosure: Nothing to disclose.